Improving Student's Speaking by Using Cocktail Party Technique in Teaching Recount Text for Senior High School Students - Ghirah Mediska; Aryuliva Adnan (Universitas Negeri Padang, 2019)
AbstractThis paper deals with the use of Cocktail Party Technique in teaching recount text for senior high school students. Cocktail Party Technique can be used by teachers in teaching recount text in order to help students improving their speaking for mastering the spoken form of recounttext. This technique is used as the solution for teachers to solve students’ problems in learning recount text. This technique encourages the students to speak in the classroom in order to improve their mastery in speaking of recount text. Cocktail Party Technique can be applied for senior high school students in Indonesia. In applying this technique, teacher needs approximately 70 minutes to take time required. It is appropriate to the grade X in senior high school which has 90 minutes for learning English language based on Indonesia Curriculum of 2013.Key words: Teaching speaking, recount text, Cocktail Party Technique.